Factor seven activating protease (FSAP) predicts response to intravenous thrombolysis in acute ischemic stroke. Issue 6 (August 2016) - Bustamante, Alejandro; Díaz-Fernández, Belén; Giralt, Dolors; Boned, Sandra; Pagola, Jorge; Molina, Carlos A; García-Berrocoso, Teresa; Kanse, Sandip M; Montaner, Joan
Background: Prediction of recanalization after intravenous thrombolysis could be important to direct secondary reperfusion techniques. Factor seven activating protease (FSAP) has been described to have a relevant pathophysiological role in stroke. Aim: The aim is to determine whether plasma FSAP levels are associated with recanalization after tissue plasminogen activator in acute stroke. Methods: FSAP antigen, activity, and FSAP-inhibitor complexes were measured in 120 acute stroke patients admitted to Hospital Vall d'Hebron with arterial occlusions, before intravenous thrombolysis. Recanalization was assessed by transcranial Doppler 2 h after thrombolysis. Predictors of recanalization were determined by logistic regression analysis and the additional predictive value of FSAP over them was determined by integrated discrimination improvement index. Results: Complete recanalization was achieved in 31 patients. FSAP antigen levels were lower in patients achieving recanalization (8.2 (6.3–11.7) µg/mL vs. 9.8 (7.6–12.8) µg/mL; p = 0.046). After adjustment by age, sex, and National Institutes of Health Stroke Scale, Oxfordshire Community Stroke Project (odds ratio = 0.33 (0.13–0.82), p = 0.017) and FSAP antigen (odds ratio = 3.22 (1.22–8.47), p = 0.018) were independently associated with recanalization, and the addition of FSAP improved the model discrimination (integrated discrimination improvement = 5.5% (1.4–9.7), p = 0.009). Conclusions: Our study showed that lower FSAP antigen plasma levels were associated with a higher chance of arterial recanalization after tissue plasminogen activator treatment, suggesting an involvement of FSAP in tissue plasminogen activator-induced clot lysis. FSAP antigen determination might be useful in predicting tissue plasminogen activator response in stroke patients.